Constructing and contesting the Olympics online: The internet, Rio 2016 and the politics of Brazilian development. (April 2014) - Millington, Rob; Darnell, Simon C
The awarding of the 2016 Summer Olympics to the city of Rio de Janeiro, Brazil continues the trend of international sports mega-events being hosted in the global South and constructed and promoted as part of long-term development plans and policies. Rio 2016 also connects with the International Olympic Committee's (IOC) current commitment to international development and global humanitarianism. In this paper, we examine the proliferation of this agenda through official online Olympic communication and compare it against critical perspectives from activist bloggers concerned with development issues specific to Rio 2016. The results support the notions that the internet can be used both to serve and challenge processes of capitalist accumulation and that political debates and contestations, such as those regarding development policy, are increasingly 'amplified' online. We argue, therefore, that while the IOC and Olympic stakeholders use the internet in support of neoliberal and modernist notions of development, online communications also offer important avenues for disseminating current critiques of, and resistance to, Olympic hosting.